Effects of Bothrops asper snake venom on lymphatic vessels: insights into a hidden aspect of envenomation - Mora Rodríguez, Javier Francisco (2008)
artículo (arbitrado) -- Universidad de Costa Rica, Instituto de Investigaciones Clodomiro Picado. 2008